2016
DOI: 10.17509/ijal.v5i2.1354
|View full text |Cite
|
Sign up to set email alerts
|

Issues of terrorism on the internet in the wave of democratization of post-reform Indonesia: A semiotic analysis

Abstract: The discourse of terrorism is a global issue but tends to be interpreted as controversial. This study sought to dismantle the controversy of meanings through the analysis of signs and meanings, with a view to explore and demonstrate the wave of democratization that took place in post-reform era in Indonesia. This study was a case study using readers' responses to terrorism issues provided by cyber media on the Internet. It also rests primarily on the semiotic theory of Peirce and the concept of democratization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…After the data is collected, data analysis is then performed which refers to the semiotic analysis of Buhler and the pragmatic Peirce semiotics developed by Hoed. Buhler and Peirce's semiotic analysis refers to the theory presented by (Saifullah, 2016). However, the difference in analysis conducted by the researcher focuses on content while the analysis of research carried out on the process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the data is collected, data analysis is then performed which refers to the semiotic analysis of Buhler and the pragmatic Peirce semiotics developed by Hoed. Buhler and Peirce's semiotic analysis refers to the theory presented by (Saifullah, 2016). However, the difference in analysis conducted by the researcher focuses on content while the analysis of research carried out on the process.…”
Section: Methodsmentioning
confidence: 99%
“…Expressive expressions on nationalism issues also vary. Verbal signs are manifested from respondent response data (Saifullah, 2016). Likewise in this study, verbal signs were obtained from the text data of respondents' responses to nationalism issues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies related to signs and meanings have been carried out (Saifullah, 2016) through this research the writer used a case study using readers' responses to terrorism issues provided by cyber media on the Internet, it was found that there was a change in structure from "Top Down" to "Bottom Up". Responses to the media while the media "seems to have no space to respond to responses from internet users".…”
Section: Semiotics-pragmaticsmentioning
confidence: 99%
“…The development of the internet has become more rapid and the internet has become an easy to use software program for uploading various contents to the internet, this has been proven in 2000 as many emerging blogs, video sharing sites, social networking site and in 2010 emerged the type of social media that is equipped with features for editing photos and videos, can exchange comments and use likes as interactions between account owners and there are comments and DM columns to send messages to each other, this social media which is now known as Instagram [2].Various information IC-HEDS 2019 can be obtained through information ranging from social, political, cultural to simple things that can become viral only through the fingertips. In the previous research [3] conclude that in virtual space is a kind of space or place to show a forum of a democratization, public participant, freedom expression and the development of the internet as a media has resulted for more debate and complaint.…”
Section: Introductionmentioning
confidence: 98%